Population viability analysis of the Taruka, Hippocamelus antisensis (D’Órbigny, 1834) (Cervidae) in southern Peru - Barrio, Javier (2007)
This study analyzes the probabilities of survival for a population of tarukas (Cervidae: Hippocamelus antisensis) in southern Peru using data gathered in the fi eld, data from other studies and the computer-based Vortex simulation program. A total of 900km2 of the northern part of the Aymara- Lupaca Reserved Zone were evaluated in 1997. The population viability analysis showed that this taruka population exhibited a high sensitivity to changes in fi rst-year mortality, immigration and fragmentation of the population. Taruka population size and survival probabilities did not exhibit sensitivity to changes in the carrying capacity of the area or to changes in environmental variation. Although the results of this study are open to alternative interpretation, the conservation and management of taruka in the Aymara-Lupaca Reserved Zone may be helped by the fi ndings of the viability analysis. Population viability analysis is a cost-effective tool in identifying factors that might affect the survival of taruka in southern Peru.